Implementasi Pendidikan Karakter Dalam Membentuk Karakter Tanggung Jawab Di SMP IT Raudhatul Ulum Sakatiga Ogan Ilir - Muhamad Oky Muhlisin; Icha Aulia R. Sormin; Mia Permata Sari; Leny Marlina; Mardiah Astuti (JIEM (Journal of Islamic Education Management), 2023)
Abstract: “This research is entitled "Implementation of Character Education in Forming Responsible Character at SMP IT Raudhatul Ulum Sakatiga Ogan Ilir". The reason the researcher took this title is because the researcher sees that there is still responsibility character education that is not yet running in accordance with the goals of character education in the school environment, where there are still students who are not used to responsibility in the school environment. The main problem in this research is how to implement character education in forming responsible character and what are the supporting and inhibiting factors in implementing character education in forming responsible character at SMP IT Raudhatul Ulum Sakatiga Ogan Ilir.This research is a qualitative descriptive study. The main informant in this research is the principal of SMP IT Raudhatul Ulum, while the supporting informants are the Head of Student Affairs who doubles as a teacher, as well as class IX students. The data collection techniques used were observation, interviews and documentation. The data obtained was then analyzed descriptively using interactive analysis techniques which included data reduction, data presentation, drawing conclusions and data validity.From the research results obtained as follows: First, the implementation of character education in forming responsible character can run with the existence of policies made by schools to form responsible character in students, not only through regulations but through activities that motivate them to have a sense of responsibility. Second, the environment also has an important role in implementing responsible character education. Third, supporting and inhibiting factors that are the reasons for implementing or not implementing responsible character education”.